Leadership, Gender, and Politics: Political Perceptions and Participation of Young Female Voters in a Presidential Primary - Mary Christine Banwart; Kelly Winfrey (Educational Considerations, 2009)
The political arena, where historically women in the United States have been under-represented, provides an important laboratory for examining leadership and gender via the candidacy of now Secretary of State Hilary Rodham Clinton, who in 2008 was the first woman to run competitively for the Democratic presidential nomination.
Keywords: candidate; female; leadership; political; Presidential primary; voters; participation; gender; identification; limitations